A note on m-factorizations of complete multigraphs arising from designs - Kiss, György (Ars mathematica contemporanea, 2015)
Some new infinite families of simple, indecomposable ?$m$?-factorizations of the complete multigraph $λ ?K_v$? are presented. Most of the constructions come from finite geometries.
Keywords: affine spaces; afini prostori; faktorizacija grafa; graph factorization; projective spaces; projektivni prostori; razpon; spread